Features Associated With Depressive Predominant Polarity and Early Illness Onset in Patients With Bipolar Disorder - García-Jiménez, Jesús; Gutiérrez-Rojas, Luis; Jiménez-Fernández, Sara; González-Domenech, Pablo José; Carretero, María D.; Gurpegui, Manuel (Frontiers in Psychiatry, 2020)
Objective: The aim of this study is to determine the prevalence of three possible diagnostic specifiers, namely predominant polarity (PP) throughout illness, polarity of the first episode and early age at onset, in a sample of bipolar disorder (BD) patients and their association with important socio-demographic, clinical and course-of-illness variables. Methods: A retrospective and naturalistic study on 108 BD outpatients, who were classified according to the PP, polarity of the first episode and early age at onset (≤ 20 years) [vs. late (>20 years)] and were characterized by their demographics, clinical data, functionality and social support, among others features. After bivariate analyses, those variables showing certain association (P value < 0.25) with the three dependent variables were entered in logistic regression backward selection procedures to identify the variables independently associated with the PP, polarity of the first episode and early age at onset. Results: The sample consisted of 75 women ad 33 men, 74% with type I BD and 26% with type II. Around 70% had depressive PP, onset with a depressive episode and onset after age 20. Depressive PP was independently associated with depressive onset, higher score on the CGI severity scale and work disability. Onset with depressive episode was associated with type II BD, longer diagnostic delay and higher score on family disability. Early age at onset (≤ 20 years) was associate with younger age, longer diagnostic delay, presence of ever psychotic symptoms, current use of antipsychotic drugs and higher social support score. Conclusions: The results of this study show that BD patients with depressive PP, onset with depression and early age at onset may represent greater severity, because they are frequently associated with variables that worsen the prognosis. Our findings match up with the conclusions of two systematic reviews and we also include a disability factor (at family and work) that has not been previously reported. This work contributes to the use of polarity and age at onset in BD patients, as it can become a useful instrument in the prognostic and therapeutic applications.